A Pilot Study on Management Practices in Dairy Farms in the Basque Country: Focus on Colostrum Feeding and Vaccination - Maddi Oyanguren; Elena Molina; Maitane Mugica; Ainara Badiola; Ana Hurtado; Gorka Aduriz; Natalia Elguezabal (Animals)
Colostrum feeding is crucial for calf rearing to guarantee passive immunity transfer (PIT) of antibodies. The present study aimed to evaluate the effect of different management practices on the calf’s immunological parameters focusing on vaccination and colostrum management. Data were gathered on management routines, vaccination programs, and antimicrobial usage. Farmers were provided with colostrum management guidelines and a digital Brix refractometer to enhance colostrum feeding practices. Colostrum quality, PIT and lymphocyte subpopulations in both colostrum and blood were analyzed for further characterization. The combined farm and laboratory data were then examined to evaluate each farm’s situation. Farmers reliably monitored colostrum quality by Brix refractometry and were able to modify colostrum management in a way that favored PIT. High-quality colostrum was linked to better PIT outcomes. Notably, Farm C, the sole non-vaccinated farm, reported higher antibiotic usage in both calves and lactating animals and showed reduced γδ T cell levels in colostrum. In conclusion, lymphocyte subpopulation content should be further studied as a trait of colostrum quality as well as of PIT. Failure to implement a vaccination program in the farm can have negative consequences on colostrum quality, as shown when analyzing both immunoglobulins and lymphocytes. This can result in a higher number of antibiotic treatments that may in turn be followed by different patterns of antimicrobial resistance.